Representation of Women’s Bodies on TikTok Social Media - Khasanah, Siti Uswatun; ., Sutinah; Budirahayu, Tuti (Journal of Urban Sociology, 2025)
A TikTok media is a popular social media platform for sharing educational and health information. In April 2023, Indonesia became the second-largest user of TikTok media globally, with 113 million users. Social media has become a popular tool for individuals to express themselves through content, such as beauty products, skincare, and diet advice. This study aims to understand the role of TikTok users in presenting their bodies through qualitative research. The research uses qualitative methods to explain and understand the research results, focusing on body types, body goals, and positive vibes. Many TikTok users use the platform to express themselves and consume body products, making them a consumer. The study highlights the importance of body representation as a representation of a person's identity in various aspects of life, as society lacks a clear body image for individuals, affecting their performance and performance. The digital representation of TikTok users is influenced by aesthetic norms and internal social effects of the platform.Keywords: TikTok media, body representation, beauty standards, visual symbols